2019
DOI: 10.21608/alexja.2019.41839
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Some Weaning Foods Made from Rice and Legumes

Abstract: Weaning is a gradual process of introducing solids foods to an infant's diet, alongside breast milk from the age of six months, since the breast feeding along cannot meet the infant nutritional requirement. in this study three composite foods were prepared from rice and some legumes (roasted soybean, roasted peanut and roasted chickpeas) ratio 70:30. The formulations were made to meet the greatest amino acid scores, the desired amount of energy and protein according to the FAO/WHO recommendation for infants. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Among these amino acids, glutamic acid was found to have the highest range, followed, in descending order, by aspartic acid and serine, which showed the lowest range. This result is consistent with the findings of Tesby Mohamed et al (2019) in the context of weaning food derived from rice and soybean blends. Ng'ong 'ola-Manani et al (2014) also reported that glutamic acid was the most abundant amino acid, followed by aspartic acid, whereas cysteine and methionine were the limiting amino acids in the blends of fermented soybean and maize.…”
Section: Non-essential Amino Acid Of the Weaning Foods Prepared From ...supporting
confidence: 92%
“…Among these amino acids, glutamic acid was found to have the highest range, followed, in descending order, by aspartic acid and serine, which showed the lowest range. This result is consistent with the findings of Tesby Mohamed et al (2019) in the context of weaning food derived from rice and soybean blends. Ng'ong 'ola-Manani et al (2014) also reported that glutamic acid was the most abundant amino acid, followed by aspartic acid, whereas cysteine and methionine were the limiting amino acids in the blends of fermented soybean and maize.…”
Section: Non-essential Amino Acid Of the Weaning Foods Prepared From ...supporting
confidence: 92%
“…Weaning is the gradual process of introducing solid foods to a baby's diet in addition to breast milk, starting at six months of age, because breast milk alone cannot provide all of the baby's nutritional needs. The baby is gradually weaned into a semi-solid food that is typically described as digestible and has a high energy density and low bulk (Tesby Mohamed et al, 2019). Infants' needs for micronutrients such as iron and zinc increase after six months of breastfeeding, which is why recent emphasis has been placed on breastfeeding for at least six months and then including complementary foods as breastfeeding contin-ues for 18 months or longer (WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Roasting and extrusion are two different thermal processing treatments which have been widely studied for producing weaning foods with encouraging results (Balasubramanian et al., 2014; Mohamed et al., 2019 ). Both roasting and extrusion are simple and common technologies that can pregelatinize starch to improve the edibility, aroma, and digestibility of cereal grains (Gahlawat & Sehgal, 2010).…”
Section: Introductionmentioning
confidence: 99%